Measuring Spin⋅⋅⋅Spin Interactions between Heterospins in a Hybrid [2]Rotaxane. Issue 14 (9th March 2017) - Boulon, Marie‐Emmanuelle; Fernandez, Antonio; Moreno Pineda, Eufemio; Chilton, Nicholas F.; Timco, Grigore; Fielding, Alistair J.; Winpenny, Richard E. P.
Abstract: Use of molecular electron spins as qubits for quantum computing will depend on the ability to produce molecules with weak but measurable interactions between the qubits. Here we demonstrate use of pulsed EPR spectroscopy to measure the interaction between two inequivalent spins in a hybrid rotaxane molecule. Abstract : Use of molecular electron spins as qubits for quantum computing will depend on the ability to produce systems with coherent quantum states and with appropriate interactions between these spins. A pulsed EPR spectroscopy RIDME sequence was used to measure a very weak interaction between two inequivalent spins in a hybrid rotaxane.